Mortality in patients with Ebstein anomaly: a two-country, population-based cohort study including 530 patients. (3rd October 2022) - Eckerstrom, F; Hjortdal, V E; Dellborg, M; Eriksson, P; Mandalenakis, Z
Abstract: Background: Low birth prevalence and referral bias constitutes significant obstacles in extending our knowledge regarding the natural history of Ebstein anomaly (EA). Purpose: In an extensive two-country register-based collaboration we aimed to investigate the survival in EA patients with respect to associated congenital cardiac malformations Methods: Patients born in the period 1970–2017 and diagnosed with EA were identified in Danish and Swedish nationwide medical registries and subsequently merged. Each EA patient was matched by birth year and gender with ten controls without congenital heart disease from the general population. Cox proportional hazard regression model and Kaplan-Meier survival function were used to compute risk of mortality (hazard ratio) and survival. Follow-up started at birth and patients became risk at time of EA diagnosis. Results: We included 530 patients and 5, 300 matched controls; median follow-up was 10.5 years (interquartile range: 3.5–20.9). In the total EA cohort, 43% (n=228) underwent cardiac surgery, predominantly EA-related surgery (81%). Approximately half of the cohort had an isolated EA (n=248), 11% (n=57) had a concomitant atrial septal defect only, and 42% (n=225) other associated congenital cardiac malformations. The 35-year survival in patients with isolated EA was 93%, superior compared with patients with concomitant atrial septal defect (ASD) (83%) and patients with other associated congenital cardiac malformations (72%), Figure 1. Patients with isolated non-operated EA had a risk of mortality of 25.6 (95% confidence interval (CI): 9.0–72.6) compared with the general population. Correspondingly, the risk in patients with surgically managed isolated EA was 21.7 (95% CI: 3.9–118.5). Patients with non-operated EA and a concomitant ASD (only) revealed a 10-fold increased risk of mortality (95% CI: 1.5–75.1) compared with the general population. The risk of mortality was substantially higher in both non-operated and operated EA patients with other associated congenital cardiac malformations, HR of 106.3 (95% CI: 31.8–335.4) and 42.6 (95% CI: 18.5–97.8), respectively. Conclusions: Concomitant congenital cardiac malformations are common in EA patients and have major influence on survival, irrespective of treatment pathway (surgical versus non-surgical). Nonetheless, isolated non-operated EA patients have a 25-fold increased risk of mortality compared with the general population. Interestingly, concomitant ASD in non-operated patients seems protective in terms of risk of mortality. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Novo Nordisk Foundation.